COMPUTATIONAL INSIGHT INTO MORINGA OLEIFERA AS EGFR-TARGETING CANDIDATES FOR HNC MANAGEMENT - Adnan Abdullah; Asti Widuri; Rizka Fahriani; Muhammad Farid; Arini Rizqa Fathanah (Yayasan Adra Karima Hubbi, 2026)
Head and neck cancer (HNC) remains a major cause of cancer-related morbidity and mortality worldwide. Although epidermal growth factor receptor (EGFR)-targeted therapies have improved treatment outcomes, their clinical effectiveness is often limited by drug resistance and adverse effects, highlighting the need for alternative therapeutic candidates. This study evaluated the potential of Moringa oleifera Lam. phytochemicals as prospective EGFR inhibitors using an integrated in silico approach. Molecular docking was performed with AutoDock Vina implemented in PyRx against the EGFR crystal structure (PDB ID: 4HJO). Ligand structures retrieved from PubChem were prepared and optimized using Open Babel prior to docking, while pharmacokinetic properties were predicted using the pkCSM web server. Among the screened compounds, brassicasterol and campesterol exhibited the strongest predicted binding affinity (?8.6 kcal/mol), followed by campestanol (?8.4 kcal/mol) and ergosterol (?8.2 kcal/mol), exceeding the docking scores of both the native ligand (?7.2 kcal/mol) and gefitinib under the same computational conditions. Interaction analysis indicated that ligand binding was primarily stabilized through hydrophobic contacts with key EGFR residues, including LEU694, VAL702, and LEU820. ADMET prediction suggested favorable intestinal absorption, acceptable physicochemical properties, blood–brain barrier permeability, and low predicted mutagenicity, although several phytosterols demonstrated potential CYP3A4 inhibitory activity. These findings provide preliminary computational evidence supporting the potential of selected Moringa oleifera phytosterols as candidate EGFR-targeting compounds. However, the results are based solely on computational predictions and require further validation through in vitro and in vivo studies before therapeutic applications can be inferred.